The Influence of Top Management Commitment on Competitive Advantage through Supply Chain Resilience, Supply Chain Digitalisation, and Supply Chain Responsiveness - Siagian, Hotlan; Basana, Sautma Ronni; Suprapto, Widjojo; Tarigan, Zeplin Jiwa Husada (UI Scholars Hub, 2026)
Research Aims: This study aims to analyse the influence of top management's commitment on competitive advantage through supply chain digitalisation, responsiveness, and resiliency. Design/Methodology/Approach: Data were collected using a five-point Likert-scale questionnaire distributed to manufacturing practitioners with a minimum supervisory position. A total of 203 valid questionnaires were analysed. Data processing was performed using SmartPLS version 4.0 to test measurement and structural models. Research Findings: The study results indicate that eight hypotheses are accepted and one is rejected. Top management commitment positively impacts supply chain digitalisation, responsiveness, and resilience. Furthermore, supply chain digitalisation and supply chain resilience both positively impact competitive advantage. However, supply chain responsiveness did not affect competitive advantage. Theoretical Contribution/Originality: This research makes a theoretical contribution to the study of digital technology adoption in supply chain management. Digital technology adoption enhances companies' competitive advantage. Managerial Implications in the South East Asian Context: In Southeast Asia, there is still low integration, limited digitalisation, and vulnerability to supply chain disruption. The results of this study provide insight into the role of top management in initiating the adoption of digital technology to strengthen resilience and supply chain responsiveness, thereby improving competitive advantage. Research Limitation and Implications: This study has limitations, particularly on the research sample, which is located in East Java, Indonesia. Hence, the study results may not be valid in other countries.